Extension of the systemic entrepreneurship intention model in university students - Díez-Echavarría, Luisa; Valencia Arias, Alejandro; Bermúdez Hernández, Jonathan; Maussa Pérez, Fausto Orlando; Urrego Marín, Maria Lucelly; Torres Velásquez, Jairo Adolfo (Serbian Journal of Management, 2019)
The extension of the Systemic Entrepreneurship Intention Model, to identify and understand the factors, and their relations, that promote university students’ entrepreneurial intention, was proposed in this paper. That is, in the long run, one of the main strategies to promote economic development. The Confirmatory Factor Analysis methodology to analyze the data collected from a self-administrative questionnaire, which was applied to students of three universities of Colombia, was performed. It was found that personal attitudes and perceived feasibility are the most influential factors when it comes to starting a business. Moreover, young people may have greater intentions of creating a company when they identify good ideas and they perceive them feasible regardless of their risk levels. It is recommended implementing this model in the context of university students in emerging economies to obtain reliable results in understanding their behavior.